UPAYA PEMENUHAN KOTA LAYAK ANAK (KLA) KELURAHAN MANGGALA KECAMATAN MANGGALA KOTA MAKASSAR (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2020)
The results showed that, the Government's efforts in fulfilling a Child-Friendly City in Manggala Village, Manggala District, Makassar City, namely: Conducting socialization about the implementation of the Child-Friendly City Program, Establishing Children's Forums to facilitate children to learn to organize and Making Thematic Parks for children's play. As for the supporting factors, namely: The existence of citizen participation such as providing criticism/suggestions and participation of personnel, facilities, and infrastructure to assist the implementation of child-friendly city programs, and Child-Friendly City Cadres helping and monitoring the community in carrying out the Child-Friendly City program, Manggala Village, Manggala District, Makassar City, While Inhibiting Factors in development KLA, namely the limited budget so that not all programs run well, the lack of employees in carrying out the Child-Friendly City program, and coordination that is not optimal so that the people of Manggala Village do not all know the Child-Friendly City program which is run in Manggala Village, Manggala District, Makassar City.